Revisiting calculation of tilt angles for double‐tilt sample holders in transmission electron microscopes - Li, Xing‐Zhong (Microscopy research and technique, 2024)
We revisited the formula related to the overall tilt angle of a specimen using a side‐entry double‐tilt sample holder in a transmission electron microscope. Initially, we examined existing formulas in the literature for calculating the overall tilt angle. Subsequently, a new formula was derived, proven to better account for the actions of the double‐tilt holder, thereby providing improved accuracy in the calculation. This newly derived formula has been implemented in the Landyne software suite. Furthermore, we demonstrated the accuracy of the new formula through examples. Research Highlights A new formula has been derived to calculate overall tilt angles for side‐entry double‐tilt holders in TEM. Overall tilt angle ε from a tilt position (α1, β1) to another tilt position (α2, β2) for double‐tilt holder on stereographic projection.